Paradigm shifts in pathophysiology and management of atrial fibrillation—a tale of the RACE trials in the Netherlands - Crijns, H. J. G. M. (Neth Heart J, 2020)
In the past 20 years the Netherlands-based RACE trials have investigated important concepts in clinical atrial fibrillation (AF). Their scope ranged from rhythm versus rate control to early or delayed cardioversion and also included early comprehensive management of AF in two trials, one focusing on early ‘upstream therapy’ and risk factor management and the other on integrated chronic nurse-led care. Studies were mostly triggered by simple clinical observations including futility of electrical cardioversion in persistent AF; many patients with permanent AF tolerating day-after-day ‘uncontrolled’ resting heart rates of up till 110 beats/min; patients being threatened more by vascular risks than AF itself; and insufficient guideline-based treatments for AF. Also the observation that recent-onset atrial fibrillation generally converts spontaneously, obviating cardioversion, triggered one of the studies. The RACE trials shifted a number of paradigms and by that could change the AF guidelines. The initial ‘shock-and-forget’ attitude made place for increased attention for anticoagulation, and in turn, broader vascular risks were recognised. In a nutshell, the adage eventually became: ‘look beyond the ECG, treat the patient’. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s12471-020-01476-0) contains supplementary material, which is available to authorized users.